Pengembangan Aplikasi Kunci Elektronik Brankas Berbasis Android dengan Mikrokontroler Berbasis Bluetooth - Rozi, Ilham Fahrul; Sakti, Dolly Virgian Shaka Yudha; Juanita, Safitri; Anif, Muhammad (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2020)
Safety deposit box areusually used to protect valuables stuff from fire and theft using analog or digital keys or a combination of both. This research makes android based electronic lock application for safety deposit box to automate safe opening and closing keys with the help of a microcontroller using Bluetooth. The Workflow of these application is an Android application will activate Bluetooth on the cell phone and send input to the arduino network microcontroller to activate the Solenoid door lock so that it can open or lock safely. The purpose of this research is to design and build an Android application for electronic keys in a safety deposit box so that it has a high level of security and has a history (log) feature to find out the user's application activities. The system development life cycle that will be used to build this application is the Waterfall method. This application will be built using Java programming language with the Basic4Android editor, the database is stored using SQLite. The conclusion of this research is that after testing concluded that the integration of network microcontrollers such as Solenoid door locks, ATmega 328, Bluetooth HC-05 and testing Android applications as electronic keys into the application security system in safety deposit box has high security, simulation tools in safety deposit box can respond which is good for users when performing commands from Android via Bluetooth in less than 5 meters, the security system has high security because it has an authentication and LOG feature to find out the user's last activity (in and out)